Internalisasi Nilai Pendidikan Agama Islam untuk Menumbuhkan Jiwa Nasionalisme Siswa di Sanggar Bimbingan Sungai Mulia 5 Gombak Kuala Lumpur - Aini, Ria; Supratno, Haris; Mahadun, Hanifuddin; Idawati, Khoirotul (Education Achievement: Journal of Science and Research, 2025)
Globalization has altered Indonesian cultural values, leading to a loss of cultural identity due to the unpreparedness of Human Resources (HR) to face these changes. Nationalism, reflected in behaviors such as maintaining harmony and respecting culture, is a sense of love for the homeland. Religious education becomes key in shaping the character of children, especially at Sanggar Bimbingan Sungai Mulia 5, Gombak, Kuala Lumpur. This research describes the nationalism spirit of the sanggar students, the process of internalizing Islamic religious education values, and the supporting and inhibiting factors in fostering the students' nationalism, especially children of undocumented Indonesian Migrant Workers (PMI). A descriptive qualitative method was used, with data collected through observation, interviews, and documentation. The results reveal that the internalization of Islamic religious education values plays a crucial role in shaping the nationalism of students at Sanggar Bimbingan Sungai Mulia 5. This process is observed through Al Ghazali's internalization efforts, which include goals, the role of educators highlighting teachers' roles in habituation and exemplary practices. The emphasized value components include itiqadiyah, amaliah, and khuluqiyah, undergoing stages of transformation, transaction, and trans-internalization of values. This study is unique in highlighting the situation of children of undocumented PMIs, who face significant challenges in accessing formal education. It offers valuable insights into how religious education can be an effective tool for fostering nationalism in such a challenging context.